Full title: peripheral venous catheter complications in children: predisposing factors in a multicenter prospective cohort study - Rim Ben Abdelaziz; Habiba Hafsi; Hela Hajji; Hela Boudabous; Amel Ben Chehida; Ali Mrabet; Khadija Boussetta; Sihem Barsaoui; Azza Sammoud; Mourad Hamzaoui; Hatem Azzouz; Néji Tebib (BMC, 2017)
Abstract Background Peripheral venous catheterization (PVC) is frequently used in children. This procedure is not free from potential complications. Our purpose was to identify the types and incidences of PVC complications in children and their predisposing factors in a developing country. Methods We conducted a prospective observational multicenter study in five pediatric and pediatric surgery departments over a period of 2 months. Two hundred fifteen PVC procedures were conducted in 98 children. The times of insertion and removal and the reasons for termination were noted, and the lifespan was calculated. Descriptive data were expressed as percentages, means, standard deviations, medians and interquartile ranges. The Chi2 test or the Fisher test, with hazard ratios and 95% confidence intervals (CI95%), as well as Student's t test or the Mann-Whitney U test were used to compare categorical and quantitative variables, respectively, in groups with and without complications. The Spearman test was used to determine correlations between the lifespan and the quantitative variables. The Kruskal Wallis test was used to test for differences in the median lifespan within 3 or more subgroups of a variable. Linear regression and logistic binary regression were used for multivariate analysis. A p-value <0.05 was considered significant. Results The mean lifespan was 68.82 ± 35.71 h. A local complication occurred in 111 PIVC (51.9%) cases. The risk factors identified were a small catheter gauge (24-gauge) (p = 0.023), the use of a volume-controlled burette (p = 0.036), a longer duration of intravenous therapy (p < 0.001), a medical diagnosis of respiratory or infectious disease (p = 0.047), the use of antibiotics (p = 0.005), including cefotaxime (p = 0.024) and vancomycin (p = 0.031), and the use of proton pump inhibitors (p = 0.004).The lifespan of the catheters was reduced with the occurrence of a complication (p < 0.001), including the use of 24-gauge catheters (p = 0.001), the use of an electronic pump or syringe(p = 0.036) and a higher rank of the intravenous device in each patient (p = 0.010). Conclusions PVC complications were frequent in our pediatric departments and are often associated with misuse of the device. These results could engender awareness among both doctors and nurses regarding the need for rationalization of the use of PVC and better adherence to the recommendations for the use of each drug and each administration method.